2010
DOI: 10.1007/s00213-010-2128-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of social isolation-induced hyperactivity

Abstract: SI-induced hyperactivity was more pronounced and robust, as compared with SI-induced PPI deficits. Furthermore, SI-induced hyperactivity might be predictive for antipsychotic efficacy, as current treatment was effective in the model. Finally, using LY404039, a compound in development against schizophrenia, we have shown that the hyperactivity assay is sensitive to potential novel mechanisms of action. Thus, SI-induced hyperactivity might be a robust and novel in vivo screening assay of antipsychotic efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…Despite there being no overall significant effect of lamotrigine on locomotor activity [F (2,31) = 2.985, p = 0.065], there was a significant housing x drug interaction [F (1,31) = 5.501, p = 0.025] over the 60min session, reflecting a reduction in activity due to lamotrigine treatment in the isolation-reared animals only (Figure 1A). Furthermore, two-way ANOVA of total activity during the first 30min (where activity differences were most marked, as often found in isolation studies; Bianchi et al, 2006; Fabricius et al, 2010; McIntosh et al, 2013) revealed a significant rearing x drug interaction [F (1,32) = 6.719, p = 0.014], but no main effect of either rearing condition or drug treatment alone (Figure 1B). Of note, post hoc analysis confirmed there was a significant increase ( p < 0.05) in locomotion in PCP-SI-V compared to control V-GH-V rats, which was significantly reduced ( p < 0.05) by the highest dose of lamotrigine (PCP-SI-L15) compared to that in PCP-SI-V rats.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…Despite there being no overall significant effect of lamotrigine on locomotor activity [F (2,31) = 2.985, p = 0.065], there was a significant housing x drug interaction [F (1,31) = 5.501, p = 0.025] over the 60min session, reflecting a reduction in activity due to lamotrigine treatment in the isolation-reared animals only (Figure 1A). Furthermore, two-way ANOVA of total activity during the first 30min (where activity differences were most marked, as often found in isolation studies; Bianchi et al, 2006; Fabricius et al, 2010; McIntosh et al, 2013) revealed a significant rearing x drug interaction [F (1,32) = 6.719, p = 0.014], but no main effect of either rearing condition or drug treatment alone (Figure 1B). Of note, post hoc analysis confirmed there was a significant increase ( p < 0.05) in locomotion in PCP-SI-V compared to control V-GH-V rats, which was significantly reduced ( p < 0.05) by the highest dose of lamotrigine (PCP-SI-L15) compared to that in PCP-SI-V rats.…”
Section: Resultsmentioning
confidence: 53%
“…In this study, lamotrigine significantly reduced hyperactivity in PCP-SI rats placed in a novel arena, a potential index of positive symptoms of schizophrenia (Fone and Porkess, 2008; Fabricius et al, 2010), but had no effect in V-GH littermates. In previous studies, the novelty-induced hyperactivity seen in GluA1 AMPA subunit knockout mice was suppressed following a 28 day dietary administration of lamotrigine (Maksimovic et al, 2014).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Fabricius and colleagues (2011) compared locomotor activity in 45 cohort replications using aGH and aSI Lister hooded rats and showed that aSI subjects were hyperactive in 44 of these cohorts (Fabricius et al, 2011). This phenotype has also been reported in aSI Long–Evans (Butler et al, 2014a; Chappell et al, 2013) and Sprague Dawley (Ishikawa et al, 2014) strains.…”
Section: Hyperlocomotion and Response To Noveltymentioning
confidence: 99%
“…As other psychostimulants, such as cocaine, have been shown to have effects on the concentrations of DA D1-like and D2-like receptors in rats (Kleven et al, 1990; Unterwald et al, 1996), and monkeys (Beveridge et al, 2009; Nader et al, 2002), these two targets were chosen for examination. Additionally, because early rearing conditions profoundly alter the expression of locomotor (Bardo et al, 1995; Bowling et al, 1993; Fabricius et al, 2011; Hoffmann et al, 2009; Shao et al, 2009; Smith et al, 1997; Varty et al, 2000) and anxiety-like behaviors (Bickerdike et al, 1993; Chappell et al, 2013; Lodge and Lawrence, 2003; Lukkes et al, 2009; McCool and Chappell, 2009; Wright et al, 1991; Yorgason et al, 2013), we hypothesized that chronic MPH treatment would produce differential effects on the expression of these behaviors.…”
Section: Introductionmentioning
confidence: 99%